PEMBERDAYAAN MASYARAKAT DALAM SISTEM PERTANIAN MINAPADI DI DESA BANJARASRI KECAMATAN TANGGULANGIN KABUPATEN SIDOARJO - Alfredo Putra Pratama; Sri Wahyuni; Agus Wahyudi (Faculty of Social and Political Science, 2021)
Sidoarjo has experienced land use changes, especially in the agricultural sector. Banjarasri is one of the areas that tends to decline in rice production. Increasing market demand optimizes agricultural land and becomes very effective through the implementation of Minapadi farming system. Minapadi combines rice and fish cultivation in one area, so that it can increase farmers' income because it is effective and efficient in terms of time and yield. The purpose of this study is to describe and analyze community empowerment program through Minapadi farming in Banjarasri. The study uses qualitative research method with a narrative approach using community empowerment theory. Data collection techniques use interview, observation, and documentation. The result shows that the economic improvement in Banjarasri community is obtained through a community empowerment program, namely Minapadi agricultural system. The first recommendation is suggested by Banjarasri government to develop Minapadi tourism village so that the community will be more prosperous. The second recommendation is also suggested by the government to invite the farmers in implementing community empowerment. Furthermore, community empowerment in the Minapadi agricultural system is effective in improving the community-level economy even though only a few farmers do this program.